Promoting assessment for learning to ensure access, equity and improvement in educational outcomes in Ghana - Kwapong, Olivia Adwoa Tiwaah Frimpong (Journal of Interdisciplinary Studies in Education, 2021)
This study looked at assessment for learning as a criteria for promoting inclusiveness and equitable access to educational opportunities in Ghana. It compared assessment for learning and assessment of learning and recommend measures to evaluate students’ performance to allow for equitable access and progression in education. The study found the deployment of assessment of learning as discriminatory, restrictive and ineffective for judging the overall worth of students after several years of learning. It is recommended that to ensure equitable access and fairness such that no child is left behind in the Ghanaian educational system, the criteria for progression of students be based on interest and academic strengths using assessment for learning approaches and not necessarily standardized tests.